2020
DOI: 10.5897/ijmms2020.1415
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical determinants of multi drug resistant tuberculosis among HIV infected patients in Tanzania

Abstract: Multi Drug Resistant Tuberculosis (MDR-TB) is a public health challenge, which itself remains a global public health problem. Its impact is worsened by co-infection with Human immunodeficiency virus (HIV). In order to institute successful TB control strategies, factors for development of MDR-TB must be understood. This study aimed to identify and describe clinical and demographic determinants for development of MDR-TB among TB patients. This was a cross sectional, hospital-based study conducted between April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In 2019, 23 persons per every 100,000 in the South Africa population were reported to have MDR-TB [ 13 , 14 ]. Regarding risk factors, recent studies conducted in Tanzania and Niger showed TB relapse , history of irregular treatment, cigarette smoking, alcohol abuse, treatment failure, underweight and HIV as leads factors of MDR-TB occurrence [ 15 , 16 ]. Beside the HIV/AIDS burden, the HIV and TB co-infection burden in Sub-Saharan Africa remains also relatively high [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, 23 persons per every 100,000 in the South Africa population were reported to have MDR-TB [ 13 , 14 ]. Regarding risk factors, recent studies conducted in Tanzania and Niger showed TB relapse , history of irregular treatment, cigarette smoking, alcohol abuse, treatment failure, underweight and HIV as leads factors of MDR-TB occurrence [ 15 , 16 ]. Beside the HIV/AIDS burden, the HIV and TB co-infection burden in Sub-Saharan Africa remains also relatively high [ 17 ].…”
Section: Introductionmentioning
confidence: 99%